Veterinary and Animal Husbandry Extension warrants as much preference as given to Research - P. V.K. Sasidhar (Journal of Agricultural Extension Management, 2025)
The acceptance or rejection of a new technology in Veterinary and Animal Husbandry Sector by the livestock rearing community depends upon the characteristics of that innovation, the quality and density of Veterinary Extension Personnel, the clientele knowledge, accessibility to technical inputs and services essential for adoption of technology (Rao et al. , 1995). The ultimate decision to adopt a particular technology depends to a great extent on the farmers’ perceptions about the technology, socio-economic factors and the need for the technology. Veterinary Scientists time and again observed that, in the teeth of availability of ameliorated Animal Husbandry technologies, the speed of their adoption in the field is very slow. Lately, it has been realised that the lack of awareness on the part of the researchers regarding the farmers’ perceptions and priorities, has led them to address the wrong problems resulting in technologies which are not suitable or relevant to the end users for whom the technologies were evolved. With the sequel, that most of the innovations developed through research remain in the laboratories without being utilised by the farming community. The researchers are given full credit to the inroads so far been made in the animal food production front and are called upon to further increase the production to meet the balance the needs of the growing population and their food habits